Modeled De Facto Reuse and Contaminants of Emerging Concern in Drinking Water Source Waters. Issue 4 (9th April 2018) - Nguyen, Thuy; Westerhoff, Paul; Furlong, Edward T.; Kolpin, Dana W.; Batt, Angela L.; Mash, Heath E.; Schenck, Kathleen M.; Boone, J. Scott; Rice, Jacelyn; Glassmeyer, Susan T.
Abstract : De facto reuse is the percentage of drinking water treatment plant (DWTP) intake potentially composed of effluent discharged from upstream wastewater treatment plants (WWTPs). Results from grab samples and a De Facto Reuse in our Nation's Consumable Supply (DRINCS) geospatial watershed model were used to quantify contaminants of emerging concern (CECs) concentrations at DWTP intakes to qualitatively compare exposure risks obtained by the two approaches. Between nine and 71 CECs were detected in grab samples. The number of upstream WWTP discharges ranged from 0 to >1, 000; comparative de facto reuse results from DRINCS ranged from <0.1 to 13% during average flow and >80% during lower streamflows. Correlation between chemicals detected and DRINCS modeling results were observed, particularly DWTPs withdrawing from midsize water bodies. This comparison advances the utility of DRINCS to identify locations of DWTPs for future CEC sampling and treatment technology testing.